Economic analysis of allogeneic hematopoietic stem cell transplantation in the Bone Marrow Transplant Center of Tunisia - Leila Achour; Chema Drira; Mohamed Zied Sboui; Ikram Fazaa; Mohamed Ali Soussi; Senda Hammami; Tarek Ben Othman; Myriam Razgallah Khrouf (Taylor & Francis Group, 2023)
ABSTRACTIntroduction: New procedures and diagnostic tests in hematopoietic stem cell transplantation (HSCT) are associated with a significant increase in costs. The last cost estimate of allogeneic HSCT done in Tunisia was in 1996 and concerned only direct medical costs. Therefore, an updated cost analysis is needed.Objective: Analysis of direct costs during the first-year post-allogeneic HSCT in two groups of patients: Bone Marrow Transplant (Allo-BMT) and Peripheral Blood Stem Cell Transplant (Allo-PBSCT) and identification of factors leading to interindividual variations in costs in order to compare these costs with the budget allocated by the payer (CNAM).Methods: Pharmacoeconomic retrospective study, concerning patients who underwent allogeneic HSCT in 2013. Clinical and unit cost data were obtained from medical and administration records.Results:This study showed that the average direct cost of allogeneic HSCT in the population during the first year reached 56 638€. The average cost of Allo-BMT was 63 612€, and Allo-PBSCT was 45 966€ (p > 0.05). The initial hospitalization counted for 88% of total direct cost with an average cost of 41 441€ in Allo-BMT and 24 672€ in Allo-PBSCT (p < 0.05). Direct medical costs represented more than 70% of total direct costs, drugs, and laboratory tests occupied the largest share. Antifungals, antitumors, and antiviral drugs were the most expensive pharmaceutical classes with a mean cost, respectively, of 4 526€; 3 737€ and 3 268€. Some clinical criteria were significantly related to total direct costs like length of aplasia (p < 0.01) and GVHD (p < 0.05). However, the type of blood disease, its risk, length of mucositis, and the treatment protocol have no effect on the costs for all allogeneic patients.Conclusion: Our results showed that the costs of Allo HSCT have exceeded by far the budget allocated by the CNAM to the center, since the 90s to this day. That's why the total reimbursement mechanism should be revised.